COMPARISON BETWEEN SUPINE POSITION VERSUS PRONE POSITION IN PERCUTANEOUS NEPHROLITHOTOMY: A SINGLE CENTERED ANALYSIS OF 623 CASES - Muhammad Nasir Jamil,; Haq, Faheem ul; Ehsan ul Islam,; Robina Shaheen,; Umer Farooq, (Journal of Ayub Medical College Abbottabad, 2022)
Background: The ideal urological method for treating complex, large renal calculi is Percutaneous nephrolithotomy (PCNL). Its instruments, surgical techniques, and positions have all been adjusted as a result of its ever-changing nature. In PCNL, the supine position is advantageous compared to the prone position due to its several advantages, including the absence of cardiopulmonary risks, fewer post operative complications and shorter operative time. This study was designed for comparison of PCNL in prone and supine positions. Methods: After receiving ethical and research committee approval, this retrospective cohort study (comparative study?) was conducted from 2015 to 2021. Out of 623 patients, PCNL in prone position was performed on 258 patients and 365 patients in modified supine position. The patients' demographics, stone size and location, number of tracts, operating time, hospital stay, stone clearance rate, and post-operative complications were all compared. Results: The gender and age of the patients, the size and number of tracts, and location of the stones were all comparable (p>0.05). Operative time for prone position was 82 min±2.49 SD VS 65 min±2.95 SD, for modified supine position, p<0.001), hospital stay was 58 hrs.±1.66 SD for prone VS 51 Hrs.±1.65 SD, for modified supine position, p<0.01) and analgesia requirements for prone position was 41% VS 23% for modified supine position, p<0.001). The stone clearance rate was 87% in supine position and 89% in the prone positioning group (p=0.47). Urinary leakage from tract site was 0.38% in prone vs. 0% in supine position and temperature >99 °F was 12.4% in prone vs. 11.3% in supine position were the most common post-operative complications. Angioembolization was not observed in either group. Blood transfusions were given to 4.26% in prone position and in 3.58% of cases in supine PCNL. Conclusion: Percutaneous nephrolithotomy in the supine position had a short operating time, short hospital stays, and less analgesia requirements than PCNL in the prone position. In view of the above findings, supine PCNL is easy, quick to perform and having less complications rate as compare to Prone PCNL.